The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1016/j.pmedr.2019.100855
|View full text |Cite
|
Sign up to set email alerts
|

Ecological determinants of respiratory health: Examining associations between asthma emergency department visits, diesel particulate matter, and public parks and open space in Los Angeles, California

Abstract: Los Angeles County (LAC) low-income communities of color experience uneven asthma rates, evidenced by asthma emergency department visits (AEDV). This has partly been attributed to inequitable exposure to diesel particulate matter (DPM). Promisingly, public parks and open space (PPOS) contribute to DPM mitigation. However, low-income communities of color with limited access to PPOS may be deprived of associated public health benefits. Therefore, this novel study investigates the AEDV, DPM, PPOS nexus to address… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 63 publications
(81 reference statements)
0
24
0
Order By: Relevance
“…They suggested that reducing exposure to DPM might serve to improve asthma outcomes. 28 In addition to air pollution, we also analyzed mean annual temperature and annual precipitation. The mean annual temperature increased slightly over study period whereas annual precipitation fluctuated during study period.…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that reducing exposure to DPM might serve to improve asthma outcomes. 28 In addition to air pollution, we also analyzed mean annual temperature and annual precipitation. The mean annual temperature increased slightly over study period whereas annual precipitation fluctuated during study period.…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, data from 13,456 children with asthma as well as air pollution data (CO, O 3 , NO 2 , SO 2 , PM 2.5, and PM 10), traffic congestion, distance to street, land cover, and agricultural products used the study area. Douglas et al examined environmental factors, asthma reports, diesel particles, and public parks in Los Angeles 16 . For this purpose, the spatial analysis of hot spots, least squares method, and weighted geographical regression were used to map high-risk areas for asthma.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, particulate matter (PM), a major component of air pollution, has caused great concern and has been associated with a reduction in pulmonary function and exacerbation of chronic respiratory diseases such as asthma and chronic obstructive pulmonary disease (COPD) 1,2 . Air pollutants also increased the incidence of various gastrointestinal diseases and liver fibrosis and increased the morbidity and mortality of lung cancer and cardiovascular diseases, making PM a threat to human health 3,4 .…”
Section: Introductionmentioning
confidence: 99%